2019
DOI: 10.1007/s00038-019-01268-3
|View full text |Cite
|
Sign up to set email alerts
|

Are socio-economic inequalities in diet and physical activity a matter of social distinction? A cross-sectional study

Abstract: Objectives To explore whether ‘distinction’, a well-known mechanism that produces and reproduces social inequalities, can explain the socio-economic gradient in healthy diet and physical activity in contemporary obesogenic environments. If this is the case, we would expect a well-established indicator of distinction, ‘highbrow’ cultural participation, to be associated with a healthy diet and physical activity, while adjusting for education and income. Methods Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…2018, Kraaykamp 2002, McLaren and Kuh 2004, Oude Groeniger et al . 2019, Oude Groeniger et al . 2017, Sato et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018, Kraaykamp 2002, McLaren and Kuh 2004, Oude Groeniger et al . 2019, Oude Groeniger et al . 2017, Sato et al .…”
Section: Discussionmentioning
confidence: 99%
“…2018, Oude Groeniger et al . 2019, Oude Groeniger et al . 2017, Pampel 2012), because of the well‐established relationship between socioeconomic position and cultural capital (Ridgeway 2014, van der Waal and de Koster 2015), and the hypothesised importance of cultural capital for maintaining a lower BMI (Abel 2008, Williams 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected by means of a large-scale postal survey in 2014, administered as the fifth wave of data collection for the longitudinal Dutch GLOBE study (response = 45.5%) [18]. A cross-sectional stratified sample of the 25–75 years old population in the city of Eindhoven was used in the analyses ( N = 2812) [20, 25]. More detailed information on the objectives, study design, and data collection of the Dutch GLOBE study can be found elsewhere [26, 27].…”
Section: Methodsmentioning
confidence: 99%
“…In the Netherlands, educational attainment is the most important dimension of segregation, and it has been shown that low and high educated people increasingly live separate lives, with different preferences and different lifestyles [15, 17]. Also, health-related behaviors differ remarkably when comparing low and high educated groups – more so than when comparing income or occupational groups [1820]. Therefore, in the Dutch context, it is especially relevant to understand how education-specific bridging social capital (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Villalonga-Olives et al [ 25 ] examined the effect of both individual- and group-level social capital on the health status of the elderly in the United States, finding race and ethnic differences. A Dutch study examined the link between “highbrow” cultural participation and health, finding that measures of “distinction” were associated with healthy diet and physical activity, net of education and income [ 26 ]. In other international publications, authors have used survey data creatively to operationalize cultural capital beyond educational attainment (such as various forms of leisure participation, types of media usage, fashion preferences, other forms of consumption tastes and preferences) and social capital (social contacts and connections as well as access to resources provided by these relationships) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%